Formal ratification of subseries for the Pleistocene Series of the Quaternary System - Head M.J.; Pillans B.; Zalasiewicz J.A.; Alloway B.; Beu A.G.; Cohen K.M.; Gibbard P.L.; Knudsen K.L.; van Kolfschoten T.; Lirer F.; Litt T.; Liu J.; et al. (International Union of Geological Sciences, 2022)
The Pleistocene Series/Epoch of the Quaternary System/ Period has been divided unofficially into three subseries/ subepochs since at least the 1870s. On 30th January, 2020, the Executive Committee of the International Union of Geological Sciences ratified two proposals approved by the International Commission on Stratigraphy formalizing: 1) the Lower Pleistocene Subseries, comprising the Gelasian Stage and the superjacent Calabrian Stage, with a base defined by the GSSP for the Gelasian Stage, the Pleistocene Series, and the Quaternary System, and currently dated at 2.58 Ma; and 2) the term Upper Pleistocene, at the rank of subseries, with a base currently undefined but provisionally dated at ~129 ka. Defining the Upper Pleistocene Subseries and its corresponding stage with a GSSP is in progress. The Middle Pleistocene Subseries is defined by the recently ratified GSSP for the Chibanian Stage currently dated at 0.774 Ma. These ratifications complete the official division of the Pleistocene into three subseries/ subepochs, in uniformity with the similarly subdivided Holocene Series/Epoch.